SISTEM PENYIRAMAN TANAMAN ANGGREK MENGGUNAKAN SENSOR KELEMBABAN DENGAN PROGRAM BORLAND DELPHI 7 BERBASIS MODUL ARDUINO UNO R3 - Widhi, Happy Nugrahaning; Winarno, Heru (Vocational School Diponegoro University, 2014)
Happy Nugrahaning Widhi, Heru Winarno, in paper orchid plant watering system using humidity sensor used Borland Delphi 7 based on arduino uno R3 explain that the utilization of variable moisture for plant watering orchids do not fully utilized. At this time watering orchids is still done manually. It certainly took a lot of time, by making a watering system based on this moisture will save time. To determine the value of temperature and humidity used SHT-11 module is capable of detecting the temperature from -40C to 123,8˚C and relative humidity from 0% RH to 100% RH. Watering plants Phalaenopsis amabilis orchids species do when the SHT-11 detects the humidity inside the orchids house below 60% RH. Watering is carried out by spraying water from above directly into the plant’s roots. The method of watering is intended that the water can be poured directly absorbed by the plant. This control system controlled by arduino uno microcontroller. As for the computer control system, used Borland Delphi 7 to make aplication for control. So this watering system is divided into two they are automated systems and control through computer system Keywords: Module SHT-11, Arduino UNO, Borland Delphi 7.